J.F.H. Claiborne papers - Claiborne, J. F. H. (John Francis Hamtramck), 1809-1884.; Claiborne, Willis Herbert, -1869.; Garrett, Henry A., 1841-1901.
Correspondence, diaries, speeches, writings, notes, business records, legal and financial documents, genealogical charts, and other papers relating principally to Democratic Party politics at the state and national level prior to the Civil War, a visit to Washington, D.C. (1824-1825), Claiborne's work as editor of several Democratic newspapers, his role as a member of the U.S. Board of Choctaw commissioners in the settlement of claims by the Choctaw Indians, his service as U.S. timber agent for Louisiana and Mississippi, slave transactions and other business matters as a plantation owner in Adams County, Miss., and personal and family affairs.
Includes a diary (1864) of Claiborne's son, Willis Herbert Claiborne, kept while serving with the Army of Tennessee at Missionary Ridge, Tenn., and a diary (1861-1869) of Claiborne's son-in-law, Henry A. Garrett, relating to his service in the Jefferson Davis Legion of the Mississippi Cavalry, to Reconstruction, and to personal and business affairs as a plantation owner in Adams County, Miss.
Correspondents include Azel Backus Bacon, Albert Gallatin Brown, William McKendree Gwin, Richard M. Johnson, James B. McRea, John A. Parker, Seargent S. Prentiss, and Robert J. Walker.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
U.S. representative from Mississippi (1835-1838), editor, and historian.
Collection material in English.
Keywords: Brown, Albert Gallatin, -- 1813-1880 -- Correspondence; Gwin, William McKendree, -- 1805-1885 -- Correspondence; Johnson, Richard M. -- 1781-1850 -- Correspondence; Parker, John A. -- Correspondence; Prentiss, S. S. -- 1808-1850 -- Correspondence; Walker, Robert J. -- 1801-1869 -- Correspondence; Claiborne family; Confederate States of America. -- Army of Tennessee; Confederate States of America. -- Army. -- Mississippi Cavalry Regiment; Democratic Party (U.S.); Choctaw Indians -- Claims; Forest policy -- United States; Indians of North America -- Government relations; Plantations -- Mississippi -- Adams County; Reconstruction (U.S. history, 1865-1877); Slavery -- Mississippi; Slave-trade -- Mississippi; Timber -- Louisiana; Timber -- Mississippi; Missionary Ridge (Tenn. and Ga.) -- History; Mississippi -- Politics and government; Tennessee -- History -- Civil War, 1861-1865.; United States -- Politics and government -- 19th century; Washington (D.C.) -- Description and travel; Mississippi -- Politics and government; Forest policy -- United States; United States -- Politics and government -- 19th century; Bacon, Azel Backus -- Correspondence; McRea, James B. -- Correspondence; Editors; Historians; Representatives, U.S. Congress -- Mississippi